ANALISIS PEMANFAATAN GADAI SAWAH DITINJAU DARI SEGI HUKUM ISLAM (DITELITI DI DESA CIJAKU KABUPATEN LEBAK BANTEN - Lu’luul Karimah, Adhiyani (An Nawawi, 2022)
In Article 1150 of the Civil Code, a pawn is a right obtained by a person who owes money to a movable property, which is handed over to him by a debtor or by another person on his behalf, and which gives the debtor the power to take repayment of the goods. with precedence over other debtors; with the exception of the cost of auctioning the item and the cost that has been incurred to save it after the item has been mortgaged, which costs should take precedence. In this study, the authors conducted interviews with several parties in order to obtain information to support and complement the materials obtained by literature study. The interviews included informants who had practiced pawning the fields, ulama figures and Cijaku Village officials. Accompanied by distributing questionnaires for pawnbrokers and pawn recipients. From this research, it can be concluded that there is an invalidity in the contract, namely sighat, because at the time of ijab-qabul it is not stated when the pawn contract will end. It is invalid if the recipient of the pawn (murtahin) does not determine the time limit for the pawn, the continuous taking of the benefits of pawning the fields will result in losses for the pawning party (rahin).